25-Hydroxyvitamin D in African-origin populations at varying latitudes challenges the construct of a physiologic norm(1)(2)(3) - Durazo-Arvizu, Ramon A (American Society for Nutrition, 2014)
Background: The vitamin D–endocrine system is thought to play a role in physiologic processes that range from mineral metabolism to immune function. Serum 25-hydroxyvitamin D [25(OH)D] is the accepted biomarker for vitamin D status. Skin color is a key determinant of circulating 25(OH)D concentrations, and genes responsible for melanin content have been shown to be under strong evolutionary selection in populations living in temperate zones. Little is known about the effect of latitude on mean concentrations of 25(OH)D in dark-skinned populations. Objective: The objective was to describe the distribution of 25(OH)D and its subcomponents in 5 population samples of African origin from the United States, Jamaica, Ghana, South Africa, and the Seychelles. Design: Participants were drawn from the Modeling of the Epidemiologic Transition Study, a cross-sectional observational study in 2500 adults, ages 25–45 y, enrolled between January 2010 and December 2011. Five hundred participants, ∼50% of whom were female, were enrolled in each of 5 study sites: Chicago, IL (latitude: 41°N); Kingston, Jamaica (17°N); Kumasi, Ghana (6°N); Victoria, Seychelles (4°S); and Cape Town, South Africa (34°S). All participants had an ancestry primarily of African origin; participants from the Seychelles trace their history to East Africa. Results: A negative correlation between 25(OH)D and distance from the equator was observed across population samples. The frequency distribution of 25(OH)D in Ghana was almost perfectly normal (Gaussian), with progressively lower means and increasing skewness observed at higher latitudes. Conclusions: It is widely assumed that lighter skin color in populations outside the tropics resulted from positive selection, driven in part by the relation between sun exposure, skin melanin content, and 25(OH)D production. Our findings show that robust compensatory mechanisms exist that create tolerance for wide variation in circulating concentrations of 25(OH)D across populations, suggesting a more complex evolutionary relation between skin color and the vitamin D pathway. This trial was registered at clinicaltrials.gov as NCT02111902.